Dover, Shawnee County - Rutledge, Jess (Kansas State University, The Chapman Center for Rural Studies, 2011)
For years, the small town of Dover has been a mere blip on the map of Kansas – in fact; it does not appear at all on some maps. Until recently, when a Dover baker won a national pie-baking contest, even residents of Shawnee County, where Dover is located, had heard little about the town. The unincorporated township, which has a population of 1,7342, lies on Kansas Highway 4 about twelve miles southwest of Topeka. Dover truly does embody the saying, “if you blink, you might miss it.” Though Dover might be lost to most Kansas residents, the town remains as a small thriving community with a rich historical background.
Jess Rutledge, “Dover, Shawnee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/51.
Keywords: Dover; Heritage Day festival; Norma Grubb; Shawnee County; Sommerset Cafe; Sommerset Shire England